Ecology and management of the coffee berry borer (Hypothenemus hampei): the potential of biological control - Natalia Moreno-Ramirez; Felix J. J. A. Bianchi; Maria R. Manzano; Marcel Dicke (BioControl, 2024)
Coffee is an important commodity in Latin America that is grown by smallholder farmers and large-scale coffee producers. The coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae: Scolytinae) is a major pest of coffee that originates from West Africa and has invaded all coffee-producing regions. With climate change, the problems that this beetle poses to coffee production are expected to increase. Controlling this pest is a true challenge and chemical insecticides still are one of the main tools used, despite the environmental and human-health issues associated with this approach. To find sustainable alternatives for chemical control of the coffee berry borer, classical biological control, augmentative biological control, and integrated pest management have received extensive attention. Parasitoids, predators, entomopathogenic fungi, and nematodes have been identified and studied for their potential to manage the infestations of this major coffee pest. Conservation biological control has recently gained more attention, but its development is still in its infancy. In this review, we examine strategies for the control of the coffee berry borer in Latin America. We identify knowledge gaps for developing sustainable biological control programs, including conservation biological control within the context of farming systems, land use in the surrounding landscape, as well as the vision of coffee growers.